A review on the impact skills analysis using two physical principles, Impulse- Momentum and Work- Energy in martial arts - Neda Boroushak; Mansour Eslami; Hasan Khoshnoodi (Biyumikānīk-i varzishī, 2017)
Objective: In order to increase the level of performance of impact skills in martial arts, based on two main physical principles of work,-energy and impulse-momentum in analyzing these skills was done.   Methods: The search of articles was carried out in specialized databases and then31 related articles selected based on entry and exit criteria were analyzed.  Results: In this study, it was specified that the energy and power used for each impact, can determine the purpose of its implementation and also examine the difference and importance of the above parameters in various sports. Also it was revealed that the most important variables in impact skills are force, linear velocity, and effective mass of the striking member that in different sport, their importance varies and the best method for measuring of impact force based on impulse-momentum is force plate.      Conclusion: The results indicate that the method of impulse--momentum is simpler and more practical but work-energy method provides more accurate and useful information in the analysis of skills for coach and athletes. Finally، further studies on the effective mass of impact, principle of impulse-momentum by considering and calculating the angular momentum and also more researches by using the work-energy are suggested.